A language competition model for new minorities. (February 2019) - Templin, Torsten
This article presents a new model describing a language competition situation between a local majority language and a migrant minority language. Migrants enter the society, form families, and produce offspring. Adults raise their children in either one of the two languages or both. Children then attend school, learn additional languages as adults, and produce a new cohort with its own linguistic repertoire. Families and adults are utility maximizing actors, who take into account instrumental aspects of languages, such as their communicative range, as well as identity-related aspects. A general macro-level model describes how the linguistic composition of a population facing migration changes over time. Furthermore, a specific functional form of the general model is proposed and steady states are analyzed. Finally, for illustrative purposes, the model is applied to the case of Spanish and English in the United States.